1988
DOI: 10.1177/019459988809900301
|View full text |Cite
|
Sign up to set email alerts
|

Provocation‐Neutralization: A Two‐Part Study Part I. The Intracutaneous Provocative Food Test: A Multi‐Center Comparison Study

Abstract: This study investigated the clinical usefulness of the intracutaneous provocative-neutralization food test (IPFT). Thirty-seven patients were tested for five identical food allergies by eight physicians in different geographical locations. Throughout the study, comparison was made between the IPFT when interpreted by skin response (IPFT SK) and when interpreted by symptom provocation (IPFT PR). Double-blind IPFT results were compared with those of previously accomplished oral challenge food tests (OCFT). IPFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The skin response alone is a more sensitive measure of food hypersensitivity than provocation of symptoms. This finding agrees with findings of previous studies 18 . When the target organ includes the vocal folds, strobo-videolaryngoscopy is a valuable additional diagnostic tool for confirming anatomic changes.…”
Section: Discussionsupporting
confidence: 92%
“…The skin response alone is a more sensitive measure of food hypersensitivity than provocation of symptoms. This finding agrees with findings of previous studies 18 . When the target organ includes the vocal folds, strobo-videolaryngoscopy is a valuable additional diagnostic tool for confirming anatomic changes.…”
Section: Discussionsupporting
confidence: 92%
“…11,12 In 1988, the American Academy of Otolaryngologic Allergy reported that the skin response was the more dependable method of test interpretation than symptom provocation, providing a validity coefficient of 0.78 and a reliability coefficient of 0.68. 5,13 There is evidence to suggest that intradermal testing rather than skin prick testing is the more sensitive testing method in food tests, as the latter technique does not deliver a big enough dose to register a response. 5 For these reasons SPTs were used for the inhaled allergens and IDFTs used for the food tests in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, intradermal tests were carried out to determine delayed food hypersensitivity as validated by King et al 9,10 The intradermal tests were conducted according to the method described by the American Academy of Otolaryngic Allergy. In this study we conducted only the provocation part of the test (ie, the first dilution, which is of the highest concentration).…”
Section: Methodsmentioning
confidence: 99%